Composites made from CF prepreg trim waste tapes using sheet molding compounds (SMC) technology: Challenges and potential. (July 2020) - Sultana, Sanzida; Asadi, Amir; Colton, Jonathan; Kalaitzidou, Kyriaki
Abstract: This study explores the use of carbon fiber (CF) prepreg trim waste to manufacture lightweight, high performance and low cost CF composites using sheet molding compound (SMC) technology. First, the modifications of a typical SMC and a flow study to determine the charge in size and mass of the sheets are determined. Then, the effect of the age of the prepreg tapes, aspect ratio of cut chips and pressure during compression molding on the tensile and impact properties of the composites is determined and these properties are compares with those of typical SMC composites. It is concluded that (i) the standard SMC production line needs to be modified in order to successfully convert CF tapes into sheets and (ii) the produced CF composites can meet the high stiffness and acceptable strength for not strength-critical applications without the need to store the prepreg trim waste in controlled conditions.